2009
DOI: 10.2209/tdcpublication.50.55
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Signal Intensity from Retrodiscal Tissue Related to Joint Effusion Status and Disc Displacement in Elderly Patients with Temporomandibular Joint Disorders

Abstract: Magnetic resonance imaging (MRI) on patients with temporomandibular joint disorders (TMD) has revealed that a decrease and/or increase in signal intensity from retrodiscal tissue, joint effusion (the excessive accumulation of joint fluid) and articular disc displacement are related to TMD. However, the effect of aging on these phenomena has yet to be clarified. This study was carried out to explore the relationship between changes in signal intensity from retrodiscal tissue, joint fluid status and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Similarly, several studies divided the levels of effusion into four or five groups (4,20,21,26). In this study, the 'present'/'absent' approach used by Manfredini et al was used (11).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies divided the levels of effusion into four or five groups (4,20,21,26). In this study, the 'present'/'absent' approach used by Manfredini et al was used (11).…”
Section: Discussionmentioning
confidence: 99%
“…Higher T2 signal intensity, due to a richer vascular supply, has been observed in the retrodiscal tissue of painful compared to painless TMJs [2,22,25]. Moreover, Kober et al [12] and Ohkubo et al [17] compared the open-and closed-mouth positions, and found that the former was better for showing the vascular content of the retrodiscal tissue. In the present study, inter-individual differences in vascular content, as shown by MR imaging, did not appear to be significant in normal young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been described as the method of choice to assess temporomandibular joint (TMJ) soft tissues [1][2][3][4] . MRI is also useful to examine cortical bone, producing results that can be compared in quality to computed tomography (CT) and cone beam computed tomography (CBCT), allowing the examination of both hard and soft TMJ tissues in one single image method [5][6][7] . The TMJ conditions usually evaluated in MRI are position and shape of the joint disc.…”
Section: Introductionmentioning
confidence: 99%